1987
DOI: 10.1152/ajprenal.1987.253.1.f188
|View full text |Cite
|
Sign up to set email alerts
|

Lithium as a marker for proximal tubular delivery during low salt intake and diuretic infusion

Abstract: Fractional lithium clearance (CLi/CIn), transit time occlusion time (e-TT/OT), and late proximal tubule fluid-to-plasma inulin ratio [1/(TF/P)In] determined by micropuncture were measured in the same kidney during 5-sec-butyl-5-ethyl-2-thiobarbituric acid (Inactin) anesthesia in rats fed either less than 2 mu eq sodium/g diet, rodent chow containing 20 mu eq sodium/g diet, or rodent chow and 0.5% NaCl to drink. Both CLi/CIn vs. e-TT/OT (r = 0.59) or 1(TF/P)In (r = 0.65) were linearly correlated at all sodium i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 0 publications
2
54
1
Order By: Relevance
“…Conversely, at high flow rates the transepithelial potential difference is reduced so that voltage-driven Li reabsorption is decreased. These results are in accord with the excellent agreement between estimates of proximal delivery determined by Li clearance, micropuncture, and occlusion time technique during volume expansion (Thomsen et al 1981;Kirchner 1987). Futhermore, this proposed mechanism for Li reabsorption in the thick ascending limb may also explain our finding that furosemide produces a marked natriuretic response in absence of changes in CLl and FEL, in volume expanded conscious rats ).…”
Section: Lithium Clearance As a Marker For Proximal Tubular Na And Wasupporting
confidence: 87%
See 1 more Smart Citation
“…Conversely, at high flow rates the transepithelial potential difference is reduced so that voltage-driven Li reabsorption is decreased. These results are in accord with the excellent agreement between estimates of proximal delivery determined by Li clearance, micropuncture, and occlusion time technique during volume expansion (Thomsen et al 1981;Kirchner 1987). Futhermore, this proposed mechanism for Li reabsorption in the thick ascending limb may also explain our finding that furosemide produces a marked natriuretic response in absence of changes in CLl and FEL, in volume expanded conscious rats ).…”
Section: Lithium Clearance As a Marker For Proximal Tubular Na And Wasupporting
confidence: 87%
“…The reduced CL, and FEL, during Na depletion is reversed by amiloride administration (Thomsen & Leyssac 1986a& 1986bBoer et al 1987;Kirchner 1987;Thomsen & Shirley 1997). Fransen et al (1992) have confirmed these findings and by free-flow micropuncture technique they demonstrated that amiloride inhibits Li reabsorption at a site beyond the early distal tubule in Na depleted rats.…”
Section: Lithium Clearance As a Marker For Proximal Tubular Na And Wamentioning
confidence: 88%
“…The large increases in FELi after frusemide in the absence of major changes in fractional proximal reabsorption in superficial nephrons could be explained if frusemide were to increase end-proximal fluid delivery disproportionately in the deep nephrons (Kirchner, 1987). If this did occur, however, it is unlikely to have resulted from a redistribution of filtration rates, since the ratio of SNGFR/total GFR following frusemide did not change significantly.…”
Section: Discussionmentioning
confidence: 98%
“…Each rat was then caged individually and fed a wet mash diet containing 15 mmol lithium chloride and 100 mmol sodium chloride (kg dry food)-'. Lithium was used as a marker for proximal sodium and water reabsorption in all clearance experiments (Thomsen, 1984) and appropriate sodium intake was provided in order to minimize lithium transport beyond the end of the proximal nephron (Thomsen & Leyssac, 1986;Kirchner, 1987). The validity of the lithium clearance method as a proximal marker under such conditions has been reviewed in detail elsewhere (Thomsen, 1984;Kirchner, 1987;Koomans, Boer & Dorhout-Mees, 1989).…”
Section: Methodsmentioning
confidence: 99%